The management of individuals with enduring moderate to severe mental health needs: a participatory evaluation of client journeys and the interface of mental health services with the criminal justice system in Cornwall - Susan Lea; Lynne Callaghan; Susan Eick; Margaret Heslin; John Morgan; Mark Bolt; Andrew Healey; Barbara Barrett; Diana Rose; Anita Patel; Graham Thornicroft (National Institute for Health Research, 2015)
Background: Existing research identified substantial gaps between NHS mental health services and the criminal justice system for individuals with enduring moderate to severe mental health needs (EMHN). A pilot study in Cornwall echoed these findings, identifying deficiencies in provision at the interface of police and mental health services. Aim: To explore the interagency management of individuals with EMHN as they come into contact with the police. Design: A mixed-methods approach within a community psychology framework to enhance the implementation of findings. Stage 1: policy review and clinical audit to identify a sample of mental health service users who were in contact with the police. Stage 2: case-linkage study of 80 service user journeys through services at the time of three types of police contact (Section 136 detention; arrest for criminal offence and contact that did not result in detention); and a health economics component including analysis of the actual cost of 55 service user journeys and enhanced service scenarios. Stage 3: local stakeholder consultation to validate and contextualise case-linkage findings, including a national event. Setting: The research site was the county of Cornwall within the organisational contexts of Cornwall Partnership NHS Foundation Trust and Devon & Cornwall Police. Sample: Proportionate stratified random sampling identified a sample of 80 cases examined in the case-linkage study from the 538 linked cases identified by the clinical audit. Data sources: Case-linkage and health economics data involved individuals' police and mental health records; stakeholder consultation data involved focus groups and interviews. Results: Of the sample of 80 cases examined, 23 individuals had been detained under Section 136 of the Mental Health Act (1983: Great Britain. Mental Health Act 1983. Chapter 20. London: The Stationery Office; 1983) (accounting for 32 detentions), 52 had been detained in custody on suspicion of an offence (accounting for 126 arrests) and 15 had non-detention contact with the police. Findings showed that where police were aware of mental health needs and individuals were on caseload of a Mental Health Team, there was increased interaction and enhanced outcomes for service users and organisations. The health economics scenario modelling suggests that enhancing services has minimal effects on individual level costs compared with current practice. Conclusions: The research revealed discrepancy in police and mental health professionals' assessment of risk and interpretation of protocol and highlighted the need for joint interagency protocols and training to improve information sharing between agencies to enhance the management of individuals with enduring moderate to severe mental health needs. Funding: The National Institute for Health Research Health Services and Delivery Research programme.